EVALUATION OF HISTOLOGICAL CHANGES IN THE UTERUS OF RATS TREATED WITH ALGINATE FILM CONTAINING 17-Β ESTRADIOL NANOPARTICLES - Koga, Adriana Yuriko; Miyoshi, Edmar; Polay, João Pedro Gambetta; Cardoso, Bianca Cristina; Farago, Paulo Vitor; Lipinski, Leandro Cavalcante (Seven Editora, 2025)
OBJECTIVE: This study aims to investigate the effect of film containing 17-β estradiol nanoparticles on uterine tissue. The primary focus is on assessing their potential as precise hormonal therapy for skin lesions in oophorectomized rats.METHODS: The research involved the development of an alginate film containing 17-β estradiol nanoparticles. The animal assay was conducted on oophorectomized rats with dorsal skin lesions measuring 4 cm². The rats were divided into three groups: one treated with the alginate film, the second with a film containing conventional 17-β estradiol, and the third with a film containing 17-β estradiol nanoparticles. Macroscopic evaluation of lesion retraction was performed, and uterine samples were stained with hematoxylin and eosin on days 7, 14, and 21.RESULTS: The results showed no significant differences in the lesion retraction area among the three groups. Qualitatively, no notable uterine alterations were observed in the estrogen-treated groups and the control group, indicating the absence of hyperplasia or malignancies. However, there were statistical differences in endometrial layer thickness, primarily related to the conventional 17-β estradiol group. Myometrial thickness analysis also showed alterations related to the nanoparticles treatment compared to the control.CONCLUSION: The incorporation of 17-β estradiol nanoparticles into the alginate film, administered topically, demonstrated minimal uterine changes. This finding underscores the potential of these nanoparticles as precise hormonal therapy with reduced systemic impact when used in the treatment of skin lesions in oophorectomized rats.DOI: https://doi.org/10.56238/sevened2025.021-026